Point spread function of the optical needle super-oscillatory lens - Rogers, Edward T. F. (2014)
Super-oscillatory optical lenses are known to achieve sub-wavelength focusing. In this paper, we analyse the imaging capabilities of a super-oscillatory lens by studying its point spread function. We experimentally demonstrate that a super-oscillatory lens can generate a point spread function 24% smaller than that dictated by the diffraction limit and has an effective numerical aperture of 1.31 in air. The object-image linear displacement property of these lenses is also investigated.